ХАЛЫҚ ШАЙЫРЛАРЫ ДӨРЕТИЎШИЛИГИНДЕ САТИРА - Давлетов, Б.А. (SCIENCE and SOCIETY, 2023)
The article analyzes satire in the works of folk poets. The ideological content and srtistry of satirical works by folk poets such as Bekjon, Sidiq, Abdiqodir, Janaboy have been thoroughly studied. Criticism of the negative vices of come people in the works, such as lying, stealing, abuse of their profession, is revealed with the help of examples.